The Y-Chromosome: Genetics of Male Infertility - Gopalan, Greeshma; Khan, Sadia Tabassum; Sharma, Ketki; Sarkar, Aparna (International Journal For Research In Health Sciences And Nursing, 2016)
Y chromosome is a specific sex chromosome, responsible for male sex determination in humans, and is inherited more or less unchanged, from paternal end to the next generation male, indefinitely. Male specific Y chromosome region or MSY of the chromosome is a non-recombining region, mainly comprising of Sex Determining region of Y (SRY) of short arm; euchromatic regions of both the arms and heterochromatic region of long arm. In the embryo the initiation of testes differentiation is controlled by the SRY region which encodes the responsible testes determining factor. The functional genes are present in the euchromatic regions whereas the heterochromatic regions lack genes. Both X and Y chromosome has same genes present in their pseudoautosomal region (PAR) due to which there are two functional copies of these genes in both men and women each, which are vital for normal development. Deletion of any of the genes in this chromosome, may therefore, account for infertility in males. Furthermore, since the Y chromosome is being inherited almost unchanged, these alterations, along with the genes may also get inherited to the next progeny. The consequences of these aberrations could be reduced fertility or infertility caused due to conditions such as oligozoospermia (significant lack of sperm) or azoospermia (complete lack of sperm) and so forth.